Enhancing Learning Concentration and Reading Comprehension in Fifth Graders: The Impact of Anticipation Guide Strategies in Elementary Education - Vira Safitri; Aprilia Tina Lidyasari (STAI Hubbulwathan Duri, 2024)
This study investigates the impact of the anticipation guide learning strategy on two key academic outcomes in elementary school students: learning concentration and reading comprehension. A quasi-experimental design with a non-equivalent control group was employed. The study involved 130 fifth-grade students from SD Gugus II Kapanewon Sewon, Bantul Regency, with a sample of 98 students selected through cluster random sampling. Data were collected using observation, questionnaires, and tests, and analyzed through descriptive statistics and inferential tests, including the McNemar test. The findings indicate that the anticipation guide strategy significantly enhances learning concentration (McNemar test, p = 0.000 0.05). Similarly, the strategy improves reading comprehension skills (McNemar test, p = 0.000 0.05). These results suggest the anticipation guide is an effective pedagogical tool for fostering both cognitive focus and literacy skills in fifth-grade students. The results highlight the dual benefits of employing anticipation guides in classroom settings, as they actively engage students and improve comprehension. The implications for elementary education underscore the importance of innovative strategies to address learning challenges in young learners. The anticipation guide learning strategy positively impacts learning concentration and reading comprehension among fifth-grade elementary students, providing a promising approach for enhancing educational outcomes in primary education. Future research should explore its applicability across different grades and subjects to broaden its utility in diverse educational contexts.